Insider Trading Patterns in Periods of Financial Crisis: A Study of the Technological Sector of Athens Stock Exchange Market - Antoniadis, Ioannis; Gkasis, Christos; Partalidou, Xanthi (International Journal of Economics and Financial Issues, 2019)
In this paper, we investigate the insider trading patterns of the Greek Stock Exchange Market before and after the outburst of the Greek Financial Crisis. Using the event study methodology, we examine and compare the relationship between insider trading and corporate governance structures, for 14 firms of the Greek Technology sector listed in ATHEX for the periods 2007-2010 and 2010-2013. Our results suggest that there are structural differences in the patterns of insider trading and the relationship that it has with the corporate governance and the ownership structure of the firms for the two time periods examined differences that should be attributed to the financial crisis. Although ownership structure does not seem to have an important effect on stock returns, separation of ownership and control, and the board of directors had a significant effect during the period of the financial crisis. Keywords: Insider Trading, Corporate Governance, Ownership Structure, Financial Crisis, Greece JEL Classifications: G11, G34 DOI: https://doi.org/10.32479/ijefi.7635